Extremely rapid isotropic irradiation of nanoparticles with ions generated in situ by a nuclear reaction. Issue 1 (December 2018) - Havlik, Jan; Petrakova, Vladimira; Kucka, Jan; Raabova, Helena; Panek, Dalibor; Stepan, Vaclav; Zlamalova Cilova, Zuzana; Reineck, Philipp; Stursa, Jan; Kucera, Jan; Hruby, Martin; Cigler, Petr
Abstract Energetic ions represent an important tool for the creation of controlled structural defects in solid nanomaterials. However, the current preparative irradiation techniques in accelerators show significant limitations in scaling-up, because only very thin layers of nanoparticles can be efficiently and homogeneously irradiated. Here, we show an easily scalable method for rapid irradiation of nanomaterials by light ions formed homogeneously in situ by a nuclear reaction. The target nanoparticles are embedded in B2 O3 and placed in a neutron flux. Neutrons captured by10 B generate an isotropic flux of energetic α particles and7 Li+ ions that uniformly irradiates the surrounding nanoparticles. We produced 70 g of fluorescent nanodiamonds in an approximately 30-minute irradiation session, as well as fluorescent silicon carbide nanoparticles. Our method thus increased current preparative yields by a factor of 102 –103 . We envision that our technique will increase the production of ion-irradiated nanoparticles, facilitating their use in various applications. Mass production of nanoparticles containing well-controlled structural defects is a challenge. Here the authors demonstrate the feasibility of homogeneous ion irradiation generated in a nuclear reactor, for the preparation of fluorescent nanodiamonds and silicon carbide nanoparticles.